Recovery of passivation (ROP) in high-nitrogen martensitic stainless steel: Preventing loss of passivation (LOP) via heat treatment - Pablo Miguel Coha-Vesga; Francisco Gil Coury; Guilherme Yuuki Koga; Martín Emilio Mendoza-Oliveros; Lais Mujica-Roncery (Journal of Materials Research and Technology)
In this work, chromium depletion and its attenuation at different tempering temperatures dictated the loss and recovery of passivation of a novel hard high-nitrogen martensitic stainless steel (HNMSS) with a significant carbon content (0.7 wt%). During tempering from 300 to 600 °C, low temperatures induced little loss of corrosion resistance due to the reduced occurrence of secondary carbides, while intermediate temperatures around 500 °C caused expanded Cr-depleted regions around the carbides, leading to a collapse in corrosion resistance attributed to the loss of passivation (LOP) occurrence. Tempering at higher temperatures, despite promoting Cr-enriched carbides, facilitated the recovery of passivation (ROP) as the diffusion processes of Cr from the martensitic matrix are enhanced at elevated temperatures, restoring much of the initial corrosion resistance of the as-quenched alloy. This work contributes to the design of HNMSS with a balanced combination of mechanical and electrochemical properties, which are essential for ensuring durable tools that are exposed to corrosion and wear threats.